Audit Tata Kelola Sistem Informasi Menggunakan COBIT 2019 pada Ombudsman Republik Indonesia - Kadek Bayu Krisna Tenggara (JATISI, 2025)
The Ombudsman of the Republic of Indonesia is a state institution authorized to supervise the delivery of public services in Indonesia. Rapid developments in information technology have significantly affected organizational objectives, thereby necessitating effective information technology governance. This study aims to evaluate IT governance at the Ombudsman of the Republic of Indonesia using the COBIT 2019 Framework as the primary assessment tool. Through a design factor assessment approach, three domains were identified as the most relevant for analysis: BAI03 (Managed Solutions Identification and Build), BAI07 (Managed IT Change Acceptance and Transitioning), and DSS01 (Managed Operations). The audit process was conducted using a questionnaire method involving four key respondents from IT-related work units, followed by analyses based on capability level assessment and gap analysis. The results indicate that all three domains are currently at Capability Level 1 (Performed Process), with average scores of 83.82%, 78.12%, and 77.78%, respectively, categorized as Largely Achieved. However, the organization’s target is to reach Capability Level 3 (Established Process), resulting in a two-level gap between the current and desired conditions. These findings suggest that while IT governance at the Ombudsman RI has established a basic level of process implementation, further improvements are required in planning, quality control, change management, and operational sustainability.